EKSPLORASI PROSES PEMECAHAN MASALAH MATEMATIKA SISWA KELAS 8 SEKOLAH MENENGAH PERTAMA DALAM MENYELESAIKAN SOAL CERITA - Luthfiyah, Indah; Simamora, Rustam Effendy; Rahayu, Setia Widia (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2024)
Mathematics researchers and educators promoted problem-solving as an essential process and skill for every student, as it was closely related to the development of students’ mathematical abilities and necessary for solving problems they encountered, both at that time and in the future. Several studies indicated that Indonesian students’ mathematical problem-solving skills remained low. This study focused on 8th-grade students at a public middle school in Tarakan, North Kalimantan, who were struggling with mathematical problem-solving. The study aimed to describe the mathematical problem-solving process carried out by the students in the 8th-grade class. Using a case study qualitative strategy, the researcher collected data through assignments, observation, document analysis, and interviews. Data analysis followed the model by Miles et al. (2014), which included data condensation, data display, and drawing conclusions and verification. The findings revealed that students’ mathematical problem-solving processes involved three main themes: understanding the problem, problem-solving strategies, and answer verification. Additionally, two supplementary themes were identified: students’ attention while facing problems and their perceptions of the mathematical problem and the provided solution. These findings highlighted the importance of educational practices that strengthened problem-solving through instruction and enhanced their self-regulation when dealing with mathematical problems.Keywords: mathematics, problem-solving, Polya, word problems. AbstrakPeneliti dan pendidik matematika mempromosikan pemecahan masalah sebagai proses dan keterampilan esensial bagi setiap siswa karena berkaitan erat dengan perkembangan kemampuan matematis siswa tersebut, dan dibutuhkan untuk memecahkan masalah matematis yang dihadapi, baik di masa sekarang maupun di masa depan. Sejumlah studi menunjukan bahwa kemampuan pemecahan masalah matematika siswa di Indonesia masih belum memuaskan. Penelitian ini berfokus pada siswa kelas 8 di sebuah sekolah menengah pertama negeri di Kota Tarakan, Kalimantan Utara, yang mengalami kesulitan dalam menyelesaikan masalah matematika. Studi ini bertujuan untuk mendeskripsikan secara mendalam proses pemecahan masalah yang dilakukan siswa di kelas tersebut. Dengan menggunakan pendekatan studi kasus kualitatif, peneliti mengumpulkan data melalui pemberian tugas, observasi, analisis dokumen, dan wawancara. Analisis data dilakukan dengan mengikuti model Miles et al. (2014), yang terdiri dari kondensasi data, penyajian data, serta penarikan kesimpulan dan verifikasi. Temuan penelitian menunjukkan bahwa proses pemecahan masalah matematika siswa mencakup tiga tema utama: pemahaman masalah, strategi penyelesaian, dan verifikasi jawaban. Selain itu, ditemukan dua tema tambahan, yaitu perhatian siswa saat menghadapi masalah dan persepsi mereka terhadap masalah serta solusinya. Temuan ini menegaskan pentingnya praktik pendidikan yang memperkuat pemecahan masalah melalui pembelajaran, serta meningkatkan pengaturan diri siswa ketika menghadapi masalah matematis.Kata kunci: matematika, pemecahan masalah, Polya, soal cerita.